2020
DOI: 10.1021/acs.est.9b06868
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Electron Shuttling Mediated by Soluble c-Type Cytochromes Produced by Shewanella oneidensis MR-1

Abstract: How metal-reducing bacteria transfer electrons during dissimilatory energy generation under electron acceptor-limited conditions is poorly understood. Here, we incubated the iron and manganese-reducing bacterium Shewanella oneidensis MR-1 without electron acceptors. Removal of soluble extracellular organic compounds (EOCs) dramatically retarded transfer of electrons to an experimental electron acceptor, Cr(VI), by MR-1. However, the return of either high MW (>3000 Da) or low MW (<3000 Da) soluble EOCs produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…[12] Recently, indications for mediated electron transfer by soluble c-type cytochromes contained in culture supernatant were found. [13] Okamoto et al [14,15] suggested a different role of flavins in the extracellular electron transport: flavin mononucleotide and RF act as co-factor of the outer membrane cytochromes MtrC and OmcA respectively and enhance their extracellular electron transfer rates. This role may explain the observed current increase in the presence of low concentrations of flavins that hardly can be accounted for by diffusive MET.…”
Section: Shewanella Oneidensis Mr-1 and Its Applications In Bioelectrochemical Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Recently, indications for mediated electron transfer by soluble c-type cytochromes contained in culture supernatant were found. [13] Okamoto et al [14,15] suggested a different role of flavins in the extracellular electron transport: flavin mononucleotide and RF act as co-factor of the outer membrane cytochromes MtrC and OmcA respectively and enhance their extracellular electron transfer rates. This role may explain the observed current increase in the presence of low concentrations of flavins that hardly can be accounted for by diffusive MET.…”
Section: Shewanella Oneidensis Mr-1 and Its Applications In Bioelectrochemical Systemsmentioning
confidence: 99%
“…However, the per cell flavin reduction rate in solution corresponding to about 2 fA [11] is only about 4 % of the current production with direct contact to the electrode of 50 fA [12] . Recently, indications for mediated electron transfer by soluble c‐type cytochromes contained in culture supernatant were found [13] . Okamoto et al [14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that ferrihydrite reduction in Shewanella relies on secreted redox mediators. 14 , 42 To explore whether the flavin-based electron mediator acts on the surface of hydrophobic minerals, we measured the secretion of water-soluble riboflavin in supernatants. In the Fh-BIC group, riboflavin accumulates rapidly at the beginning.…”
Section: Resultsmentioning
confidence: 99%
“…It could be a critical framework of METN that makes the “microcosm-to-microcosm” communication possible. However, unlike DIET, progress on IIET has been slow to sufficient, considering that the vast candidates for electron shuttles ranged from artificial additives (e.g., H 2 , biochar, and flavins) to microbial secreta (e.g., soluble c -type cytochromes) ( Liu et al, 2020 ; Wu et al, 2020 ; Zavarzina et al, 2020 ). Overall, such “top-down” strategies mainly focus on modifying and optimizing the natural-given properties of EAM, whereas how to piece together those nature-given properties is still a fundamental question awaiting an answer.…”
Section: Discussionmentioning
confidence: 99%